Studi Kasus tentang Implikasi Hukuman terhadap Kedisiplinan Siswa - Saqinah Aifi Kirmala; Arini Rehulina Br Surbakti; Fatma Angraini Lubis; Nur Cahyu Azizah; Anisa Amelia Purba; Ulan Dari; Jamaludin Jamaludin; Sri Yunita (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
Student discipline is a crucial aspect in the world of education that directly affects the effectiveness of the learning process. This study aims to analyze the implications of punishment on student discipline using a behaviorist learning theory approach. In this theory, punishment functions as a consequence that reduces unwanted behavior, while positive reinforcement aims to encourage expected behavior. A case study of Mrs. Supriyani, a teacher accused of committing violence against students, is the focus of this study. The results of the study indicate that punishment given appropriately and consistently can build a deterrent effect and increase student discipline. However, excessive or unfair punishment tends to have negative impacts, such as emotional resistance and damaged teacher-student relationships. To achieve more effective discipline, a combination of educational punishment and positive reinforcement is needed so that students not only understand the bad consequences of violations but are also motivated to demonstrate good behavior. Prospects for further development of this research include the implementation of restorative justice methods in conflict resolution and strengthening the role of teachers as learning facilitators who educate without having to cause fear.